‘Men More Polite Than Women?': Gender Differences Study of Bimanese Interaction in Requesting - Khatimah, Khusnul; Ma’ruf, Amir; Sulistyowati, Sulistyowati (Jurnal Community, 2024)
This study examines gender differences in request speech and politeness, focusing on how men and women use different linguistic strategies to convey requests politely. This study aims to analyze the alerter and supporting speech elements in request speech in the Bima language as spoken by male and female students. It also compares the request speech elements used by men and women. Using a qualitative approach, the data analyzed consists of request utterances in the Bima language. Data were collected through recording techniques and discourse completion tests. The data analysis involved categorizing the speech elements as units of analysis, focusing on alerter and supporting elements, and classifying them based on Blum-Kulka’s framework. The analysis revealed that male speech tended to demonstrate familiarity with the interlocutor through the varied use of alerter greetings, while female speech showed politeness by employing supporting speech. This difference indicates that men are more inclined to use positive politeness strategies, whereas women tend to use negative politeness strategies.